SOSIALISASI CAPACITY BUILDING LEADERSHIP DALAM UPAYA PENINGKATAN MUTU SATUAN PENDIDIKAN - Toto Suryadi; Ita Yunita; M. Asif Nur Fauzi (Institut Teknologi dan Bisnis Swadharma, 2025)
Strengthening leadership capacity is key to continuously improving the quality of educational institutions. This community service activity aimed to disseminate the concept and practice of capacity-building leadership to principals, vice principals, and educators, equipping them as agents of change in the educational environment. The implementation method included material delivery, interactive discussions, and case studies based on real-life problems in educational institutions. The dissemination material covered understanding of transformative leadership, educational quality management, data-driven decision-making, and strategies for building a collaborative and innovative work culture. The results demonstrated an increased understanding among participants of the importance of adaptive and visionary leadership in driving improvements in the quality of learning and school management. This activity is expected to be the first step in building a more resilient educational ecosystem that is responsive to the challenges of the times.Penguatan kapasitas kepemimpinan (Capacity building leadership) menjadi kunci dalam upaya peningkatan mutu satuan pendidikan secara berkelanjutan. Kegiatan pengabdian kepada masyarakat ini dilaksanakan dengan tujuan untuk menyosialisasikan konsep dan praktik Capacity building leadership kepada para kepala sekolah, wakil kepala sekolah, dan tenaga pendidik sebagai agen perubahan di lingkungan pendidikan. Metode pelaksanaan kegiatan meliputi penyampaian materi, diskusi interaktif, dan studi kasus berbasis permasalahan nyata di satuan pendidikan. Materi sosialisasi mencakup pemahaman tentang kepemimpinan transformatif, manajemen mutu pendidikan, pengambilan keputusan berbasis data, serta strategi membangun budaya kerja kolaboratif dan inovatif. Hasil kegiatan menunjukkan peningkatan pemahaman peserta terhadap pentingnya kepemimpinan yang adaptif dan visioner dalam mendorong peningkatan kualitas pembelajaran dan pengelolaan sekolah. Kegiatan ini diharapkan dapat menjadi langkah awal dalam membangun ekosistem pendidikan yang lebih tangguh dan responsif terhadap tantangan zaman